Design of ultrasonic detection device for train air leakage based on intelligent inspection robot system platform - WANG Wenchao; WANG Junping; DING Jianming; ZHU Qianyi; CHEN Xinan (机车电传动)
The increasing demand for transportation by the public has directly promoted the opening and expansion of train services and routes, which has also led to increasing pressure on the daily inspection work for trains. As an important part of ensuring train braking safety, the tightness detection of air braking pipeline is indispensable in daily train inspection. To meet practical needs and address deficiencies in the current capabilities of intelligent inspection robots, this paper introduced a dual-arm robot platform. Based on the principle of turbulence generated by small leakage holes and the subsequent generation of ultrasonic waves, a "one board, two ends" structural design was adopted to design and develop an ultrasonic detection device for air leakage. The design focused on the structure and hardware configuration of the device from the aspects of signal acquisition, signal amplification and filtering preprocessing capabilities. In addition, an algorithm for air leakage detection was designed based on FFT and the Parseval's theorem. By simulating the air leakage conditions of small holes with different diameters (0.125 mm, 0.200 mm and 0.400 mm) under different conditions, the experimental prototype was verified to be able to receive and correctly judge air leakage signals within a range of 50° cone angle and 600 mm distance in a 0.3 s acquisition time.